Quality evaluation of gnocchi pasta prepared with orange-fleshed sweet potato (Bioscience Journal, 2016)
Considering the increase of pasta market and the importance of orange-fleshed sweet potato (OFSP) nutritional value and economic aspects, this study aimed to evaluate the effect of the addiction of OFSP and potato starch on the physical characteristics of gnocchi pasta during cooking, as well as to determine the chemical and sensory characteristics of the best samples, analyzing them during storage. A central composite rotational 2nd order experimental design was employed to investigate the effects of adding 63.65% to 75.81% OFSP and 35.86% to 64.14% potato starch during the cooking of the pasta. The best treatments were analyzed for acceptability, chemical composition and behavior during storage. The addition of OFSP affected only the cooking time by causing an increase in this value. Moreover, it positively contributed to the acceptability of the product, especially the color, as well as to the increase of the fiber and ash contents. It is recommended to consume immediately after preparation. If storage is necessary, the refrigeration at 4°C is suggested, provided that packaging requirements are met, preferably vacuum packaging.